ANALISIS STRATEGI DAN MANAJEMAN EKSPOR PRODUK HORTIKULTURA DI PT. BUMI SARI LESTARI TEMANGGUNG - Mega ratri ayu aksani; Muhammad Yusuf; Nurhidajah Nurhidajah (Universitas Muhammadiyah Semarang, 2016)
This study aims to determine the marketing strategy and management of PT. Bumi Sari Lestari is precise and competitive by first identifying, assessing internal factors of company and external environment that influence the company. This is done by using the method of SWOT Analysis (Strength, Weakness, Oppurtunity, Threat) triggered by Freddy and Rangkuti. SWOT analysis is an analysis used to evaluate opportunities and threats within the business environment as well as the strengths and weaknesses of the company's internal. This research is conducted by survey method (interview and questioner) at General Manager with company company marketing staff, company agronomist staff and production staff. The result is then tested using isntrumen test (validity and reliability), hypothesis test (simple linear regression and t test (partial)) and analyzed by SWOT Analysis method. Internal factors, external, position and type of business and corporate strategy is an independent variable, which means each variable is not done comparison, but explain each other and affect other variables. The results show that the company's marketing strategy is a strategy of mutual trust, where the position of the company is in a less secure position because there will be many competitors in this business and this business is an ideal business. Companies can use the company's previous strategy by improving some of the company's weaknesses and avoiding or defending against corporate threats by creating more competitive strategies.